APPLYING MATERIALS OF AN EFL WRITING COURSEWARE FOR 8TH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Jumbuh Prabowo (Journal of English Language Studies, 2016)
To fulfill the demand of the advance of Information Technology, this present study involved multimedia for writing courseware. This study examined teacher’s and students’ responses to the use of interactive multimedia. The participants of this were one immersion class of 8th grade students and an English teacher of a junior high school in Purwokerto, Central Java. These students were selected purposively. There were two instruments used in this study: questionnaire and observational sheet. It can be concluded that regarding to the teacher’s and students’ responses to the use of interactive multimedia, it is found out that both teacher and the students responded positively. They were interested in the courseware because this multimedia was different from those used in class.